Effects of ocean acidification on pelagic carbon fluxes in a mesocosm experiment - Spilling, Kristian; Schulz, Kai G.; Paul, Allanah J.; Boxhammer, Tim; Achterberg, Eric P.; Hornick, Thomas; Lischka, Silke; Stuhr, Annegret; Bermudez, Rafael; Czerny, Jan; Crawfurd, Kate; Brussaard, Corina P. D.; et al. (Biogeosciences, 2016)
About a quarter of anthropogenic CO2 emissions are currently taken up by the oceans, decreasing seawater pH. We performed a mesocosm experiment in the Baltic Sea in order to investigate the consequences of increasing CO2 levels on pelagic carbon fluxes. A gradient of different CO2 scenarios, ranging from ambient (similar to 370 mu atm) to high (similar to 1200 mu atm), were set up in mesocosm bags (similar to 55m(3)). We determined standing stocks and temporal changes of total particulate carbon (TPC), dissolved organic carbon (DOC), dissolved inorganic carbon (DIC), and particulate organic carbon (POC) of specific plankton groups. We also measured carbon flux via CO2 exchange with the atmosphere and sedimentation (export), and biological rate measurements of primary production, bacterial production, and total respiration. The experiment lasted for 44 days and was divided into three different phases (I: t0-t16; II: t17-t30; III: t31-t43). Pools of TPC, DOC, and DIC were approximately 420, 7200, and 25 200 mmol Cm-2 at the start of the experiment, and the initial CO2 additions increased the DIC pool by similar to 7% in the highest CO2 treatment. Overall, there was a decrease in TPC and increase of DOC over the course of the experiment. The decrease in TPC was lower, and increase in DOC higher, in treatments with added CO2. During phase I the estimated gross primary production (GPP) was similar to 100 mmol C m(-2) day(-1), from which 75-95% was respired, similar to 1% ended up in the TPC (including export), and 5-25% was added to the DOC pool. During phase II, the respiration loss increased to similar to 100% of GPP at the ambient CO2 concentration, whereas respiration was lower (85-95% of GPP) in the highest CO2 treatment. Bacterial production was similar to 30% lower, on average, at the highest CO2 concentration than in the controls during phases II and III. This resulted in a higher accumulation of DOC and lower reduction in the TPC pool in the elevated CO2 treatments at the end of phase II extending throughout ...